2017
DOI: 10.1021/jacs.7b04422
|View full text |Cite
|
Sign up to set email alerts
|

Chemically Functionalized Phosphorene: Two-Dimensional Multiferroics with Vertical Polarization and Mobile Magnetism

Abstract: In future nanocircuits based on two-dimensional (2D) materials, the ideal nonvolatile memories (NVMs) would be based on 2D multiferroic materials that can combine both efficient ferroelectric writing and ferromagnetic reading, which remain hitherto unreported. Here we show first-principles evidence that a halogen-intercalated phosphorene bilayer can be multiferroic with most long-sought advantages: its "mobile" magnetism can be controlled by ferroelectric switching upon application of an external electric fiel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
101
2
2

Year Published

2018
2018
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 126 publications
(106 citation statements)
references
References 46 publications
1
101
2
2
Order By: Relevance
“…So there will be six equivalent anchoring sides that are the vertexes of a hexagon (e.g., K point as shown in Figure 3). As such, NiCl 2 (C 2 N) 6 is 2D multiferroics [31] with a switchable polarization, where the spin distribution will also be altered upon FE switching (see Figure S5 c) The change of in-plane polarization ΔP versus strain for ZnCl 2 (C 2 N) 6 and MgCl 2 (C 2 N) 6 . For example, as displayed in Figure 3a, FE switching of NiCl 2 (C 2 N) 6 can be achieved when the Ni ions are driven from K to K′.…”
Section: Resultsmentioning
confidence: 99%
“…So there will be six equivalent anchoring sides that are the vertexes of a hexagon (e.g., K point as shown in Figure 3). As such, NiCl 2 (C 2 N) 6 is 2D multiferroics [31] with a switchable polarization, where the spin distribution will also be altered upon FE switching (see Figure S5 c) The change of in-plane polarization ΔP versus strain for ZnCl 2 (C 2 N) 6 and MgCl 2 (C 2 N) 6 . For example, as displayed in Figure 3a, FE switching of NiCl 2 (C 2 N) 6 can be achieved when the Ni ions are driven from K to K′.…”
Section: Resultsmentioning
confidence: 99%
“…The vertical polarization of TiP/VP in bilayer MoS 2 is greatly enhanced compared with that in bilayer CrI 3 (see Table 2), which are respectively 3.8 and 3.0 × 10 −12 C m −1 in 2D, much higher than previous values predicted in bilayer BN and InSe. [29] The transmission will be nonmagnetic semiconducting when MP molecules bind with the upper layer, but spin-polarized and n-doped when binding with the lower layer. Sci.…”
Section: Resultsmentioning
confidence: 99%
“…Based on first‐principles calculation, Yang et al have shown that halogen‐decorated phosphorene bilayer can be multiferroic with vertical polarization and “mobile” magnetism . The vertical polarization results from the breaking of inversion symmetry by covalent bonds and switchable by the hopping of halogen adatoms between bilayers.…”
Section: Exploration Of Low‐dimensional Multiferroic Materialsmentioning
confidence: 99%
“…(a) Design of high‐density two‐dimensional multiferroic tunnel junction array and field‐effect transistor based on halogen‐decorated phosphorene bilayer with vertical polarization and “mobile” magnetism. (Reprinted with permission from Reference . Copyright 2017 American Chemical Society) (b) Side and top views of the structural model for multiferroic CH 2 OCH 3 ‐functionalized germanene layer.…”
Section: Exploration Of Low‐dimensional Multiferroic Materialsmentioning
confidence: 99%